MECHANISMS IN ENDOCRINOLOGY: Update on pathogenesis of primary adrenal insufficiency: beyond steroid enzyme deficiency and autoimmune adrenal destruction. Issue 3 (September 2017) - Flück, Christa E
Abstract : Primary adrenal insufficiency (PAI) is potentially life threatening, but rare. In children, genetic defects prevail whereas adults suffer more often from acquired forms of PAI. The spectrum of genetic defects has increased in recent years with the use of next-generation sequencing methods and now has reached far beyond genetic defects in all known enzymes of adrenal steroidogenesis. Cofactor disorders such as P450 oxidoreductase ( POR ) deficiency manifesting as a complex form of congenital adrenal hyperplasia with a broad clinical phenotype have come to the fore. In patients with isolated familial glucocorticoid deficiency (FGD), in which no mutations in the genes for the ACTH receptor ( MC2R ) or its accessory protein MRAP have been found, non-classic steroidogenic acute regulatory protein ( StAR ) and CYP11A1 mutations have been described; and more recently novel mutations in genes such as nicotinamide nucleotide transhydrogenase ( NNT ) and thioredoxin reductase 2 ( TRXR2 ) involved in the maintenance of the mitochondrial redox potential and generation of NADPH important for steroidogenesis and ROS detoxication have been discovered. In addition, whole exome sequencing approach also solved the genetics of some syndromic forms of PAI including IMAGe syndrome ( CDKN1C ), Irish traveler syndrome ( MCM4 ), MIRAGE syndrome ( SAMD9 ); and most recently a syndrome combining FGD with steroid-resistant nephrotic syndrome and ichthyosis caused by mutations in the gene for sphingosine-1-phosphate lyase 1 ( SGPL1 ). This review intends do give an update on novel genetic forms of PAI and their suggested mechanism of disease. It also advocates for advanced genetic work-up of PAI (especially in children) to reach a specific diagnosis for better counseling and treatment.